Bile Acid Receptor Therapeutics Effects on Chronic Liver Diseases - Meadows, Vik; Kennedy, Lindsey; Kundu, Debjyoti; Alpini, Gianfranco; Francis, Heather (Frontiers in Medicine, 2020)
In the past ten years, our understanding of the importance of bile acids has expanded from fat absorption and glucose/lipid/energy homeostasis into potential therapeutic targets for amelioration of chronic cholestatic liver diseases. The discovery of important bile acid signaling mechanisms, as well as their role in metabolism, has increased the interest in bile acid/bile acid receptor research development. Bile acid levels and speciation are dysregulated during liver injury/damage resulting in cytotoxicity, inflammation and fibrosis. An increasing focus to target bile acid receptors, responsible for bile acid synthesis and circulation, such as Farnesoid X receptor and apical sodium bile acid transporter to reduce bile acid synthesis have resulted in clinical trials for treatment of previously untreatable chronic liver diseases such as nonalcoholic steatohepatitis and primary sclerosing cholangitis. This review focuses on current bile acid receptor mediators and their effects on parenchymal and non-parenchymal cells. Attention will also be brought to the gut/liver axis during chronic liver damage and its treatment with bile acid receptor modulators. Overall, these studies lend evidence to the importance of bile acids and their receptors on liver disease establishment and progression.